2000
DOI: 10.1207/s1532785xmep0201_3
|View full text |Cite
|
Sign up to set email alerts
|

Violent Comic Books and Perceptions of Ambiguous Provocation Situations

Abstract: This study investigated the effects of reading very violent versus mildly violent comic books on the interpretation of ambiguous provocation situations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
(26 reference statements)
2
15
0
Order By: Relevance
“…Thus, one possibility for the increase in aggressive behavior following video game play ) is that there is a greater likelihood of responding to a variety of provocation situations with aggression. In fact, research has demonstrated that individuals who are depressed (Quiggle, Garber, Panak, & Dodge, 1992) or are high in trait anger (Kirsh & Olczak, 2000) interpret ambiguous provocation situations (i.e., an individual gets hurt, but the intent of the provocateur may be either benign or malevolent) as stemming from hostile intent. Consistent with this finding that violent video game exposure influences attentional bias, research on mood congruent memory suggests that individuals with a negative mood are more likely to remember negatively valenced information better than other emotionally valenced information (Fiedler, Nickel, Muehlfriedel, & Unkelbach, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one possibility for the increase in aggressive behavior following video game play ) is that there is a greater likelihood of responding to a variety of provocation situations with aggression. In fact, research has demonstrated that individuals who are depressed (Quiggle, Garber, Panak, & Dodge, 1992) or are high in trait anger (Kirsh & Olczak, 2000) interpret ambiguous provocation situations (i.e., an individual gets hurt, but the intent of the provocateur may be either benign or malevolent) as stemming from hostile intent. Consistent with this finding that violent video game exposure influences attentional bias, research on mood congruent memory suggests that individuals with a negative mood are more likely to remember negatively valenced information better than other emotionally valenced information (Fiedler, Nickel, Muehlfriedel, & Unkelbach, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For the current study, responses were summed to create a total trait aggressiveness score. Previous research has shown that individuals high in trait anger and hostility process social information more negatively than individuals low in trait anger and hostility (e.g., Epps & Kendall, 1995;Kirsh & Olczak, 2000). Thus, the summary score from the AQ will be entered as a covariate in subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research suggests this is the case. For instance, studies involving comic books (Kirsh & Olczak, 2000) and video games (Lynch, Gentile, Olson, & van Brederode, 2001) have demonstrated links between media violence and inferring hostile intent to the actions of another, even though the intent of that individual is unclear (Dill, Anderson, Anderson, & Deuser, 1997;Dodge, 1980). Dodge (1986) contends that individuals act aggressively and perceive hostility (when none is present) due to biases in social information processing (SIP).…”
mentioning
confidence: 99%